Pengaruh Pendidikan Kesehatan De Pengaruh Pendidikan Kesehatan dengan Pengetahuan Remaja Tentang Infeksi Menular Seksual (IMS): The Influence of Health Education on Adolescent Knowledge About Sexually Transmitted Infections (STI) - Asti Puspita; Veftisia, Vistra (Indonesian Journal of Midwifery (IJM), 2023)
Adolescent Sexually Transmitted Infections in 2018 in Semarang City, namely 1,233 people, this high number is due to the lack of knowledge of adolescents about sexually transmitted infections. Efforts are made to increase this knowledge by providing health education to adolescents. Al Ashor Vocational School was chosen as the research location because it is one of the schools in Central Java Province that has never conducted counseling related to education and knowledge of sexually transmitted infections (STI). Knowing the effect of health education on Sexually Transmitted Infections at Al Ashor Vocational High School, Gunung Pati District, Semarang City. This type of research is a quasi-experimental design with one group pretest-posttest. The population of this study were grades 10 and 11 of 126 respondents and a sample of 20 respondents, the sampling technique was purposive random sampling, the data collection tool used a questionnaire, the analysis test used a paired t test. The results showed that there was an increase in the average pretest and posttest scores from 21.70 to 26.70 with a difference in the average value of 5.00 and indicated by a p-value of 0.000 <0.05, so Ho was rejected. There is the influence of health education on adolescent knowledge about sexually transmitted infections at Al Ashor Vocational High School, Gunung Pati District, Semarang City.   Abstrak Infeksi Menular Seksual remaja pada tahun 2018 di Kota Semarang yaitu 1.233 jiwa, tingginya angka tersebut karena kurangnya pengetahuan remaja tentang infeksi menular seksual. Upaya yang dilakukan untuk meningkatkan pengetahuan tersebut dengan memberikan pendidikan kesehatan kepada remaja. SMK Al Ashor dipilih sebagai tempat penelitian karena merupakan salah satu sekolah di Provinsi Jawa Tengah yang  belum pernah melaksanakan  pengadakan menyuluhan terkait dengan pendidikan dan pengetahuan infeksi menular seksual (IMS). Mengetahui pengaruh pendidikan kesehatan tentang Infeksi Menular Seksual Di SMK Al Ashor Kecamatan Gunung Pati Kota Semarang. Jenis penilitian ini adalah quasi eksperimental dengan desain one grup pretest-posttest. Populasi penelitian ini adalah kelas 10 dan 11 sebanyak 126 responden dan sampel sebanyak 20 responden, teknik pengambilan sampel dengan purposive random sampling, alat pengumpulan data menggunakan kuesioner, uji analisis menggunakan paired t test. Hasil penelitian menunjukan adanya peningkatan nilai rata-rata pretest dan posttest dari 21,70 menjadi 26,70 dengan selisih nilai rata-rata 5,00 dan ditunjukan dengan nilai p-value sebesar 0,000 < 0,05 maka Ho ditolak. Terdapat pengaruh pendidikan kesehatan terhadap pengetahuan remaja tentang infeksi menular seksual di SMK Al Ashor Kecamatan Gunung Pati Kota Semarang.